ANALYSIS STUDENTS' PERCEPTIONS OF FULL DAY SCHOOL AND THE CONSTRAINTS MADE IN CLASS V OF THE CLUSTER II ELEMENTARY SCHOOL TAMPAN DISTRICT PEKANBARU CITY - Rafita Syafitri (Jurnal PAJAR (Pendidikan dan Pengajaran), 2020)
This study aims to determine students' perceptions of full day school and the constraints made in class V of the Cluster II Elementary School, Tampan District, Pekanbaru City. The population in this study amounted to 291 students. Samples were used as many as 80 students taken using cluster sampling techniques. Data were collected using the questionnaire method / questionnaire supported by unstructured interviews, the data analysis used was descriptive. The results showed that students' perceptions of full day school in class V elementary school group II Tampan District Pekanbaru City showed a good category of 77%. The obstacle faced by students is that there are a number of school facilities that are lacking so that sometimes it makes students feel bored and less concentrated because of studying all day long. Efforts that can be made by the school and teachers to reduce the boredom of students in attending learning in the school all day, the school can add facilities if one is lacking, one of them is air conditioning and some plants so that the school atmosphere feels comfortable and for teachers to provide good distractions in the form of games, fun learning methods and outdoor learning activities according to the subjects so that students feel happy in learning and can create active and fun learning.